1997
DOI: 10.1136/gut.41.5.669
|View full text |Cite
|
Sign up to set email alerts
|

Do patients with irritable bowel syndrome in primary care really differ from outpatients with irritable bowel syndrome?

Abstract: Results-The outpatient group contained significantly more men, reported more severe abdominal pain, more frequent complaints, more interference with daily activities, and a higher degree of avoidance of activities (p<0.01) than the primary care group. When each sex was analysed separately, these diVerences remained for female (p<0.01) but not for male patients. Outpatients were more likely to attribute their complaints to somatic causes (p<0.01), whereas primary care patients were more likely to attribute thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
1
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 26 publications
5
37
1
3
Order By: Relevance
“…27,28 A current problem with hypnotherapy and CBT is their limited availability, and that few GPs would consider referral to such treatment. 29,30 Our findings suggest, in contrast to what has been reported in referred patients, 31 that such intervention will be welcomed by patients with IBS and excessive comorbidity, since the majority related their abdominal complaints to stress and psychological factors. Patients with IBS and few or no other bodily symptoms (low comorbidity) were characterized by apparently normal psychological profiles, HRQoL, adverse life events and ability to work.…”
Section: Discussioncontrasting
confidence: 54%
“…27,28 A current problem with hypnotherapy and CBT is their limited availability, and that few GPs would consider referral to such treatment. 29,30 Our findings suggest, in contrast to what has been reported in referred patients, 31 that such intervention will be welcomed by patients with IBS and excessive comorbidity, since the majority related their abdominal complaints to stress and psychological factors. Patients with IBS and few or no other bodily symptoms (low comorbidity) were characterized by apparently normal psychological profiles, HRQoL, adverse life events and ability to work.…”
Section: Discussioncontrasting
confidence: 54%
“…13 Patients referred to secondary care have greater symptom severity than those retained in primary care and also attribute their symptoms less to stress than do primary care patients. 76 This is in keeping with the findings of a prospective study conducted in UK primary care where referral to a specialist could be predicted by the patient's denial of a role of stress, undergoing multiple testing in primary care and reporting frequent bowel movements. 77 Many of the patients seen in general practice feared that they had cancer and the authors reported that multiple testing may have prolonged their anxiety, citing a paper that emphasises the double-edged nature of normal tests.…”
Section: Introductionsupporting
confidence: 52%
“…22 Physiological factors Altered somatovisceral sensitivity and motor dysfunction of the intestine are thought to be possible pathophysiological mechanisms involved in 23 24 altered afferent processing, and altered pain threshold to gut distension 25 26 have all been implicated. However, studies are conflicting with problems of reproducibility probably related to patient selection, sedation, and methodological differences.…”
Section: Psychological Factorsmentioning
confidence: 99%